Correction to: Prognostic impact of immune gene expression signature and tumor infiltrating immune cells in localized clear cell renal cell carcinoma. Issue 1 (22nd October 2019) - Ghatalia, Pooja; Gordetsky, Jennifer; Kuo, Fengshen; Dulaimi, Essel; Cai, Kathy Q.; Devarajan, Karthik; Bae, Sejong; Naik, Gurudatta; Chan, Timothy A.; Uzzo, Robert; Hakimi, A. Ari; Sonpavde, Guru; et al.
Abstract : Following publication of the original article [1], the author reported that the current funding section "Kidney Cancer Association Young Investigator Grant provided funding for this project" should be replaced with "Kidney Cancer Association Young Investigator Grant and Bucks County Board provided funding for this project."